Acceptance of silent piling technology among local authorities in Malaysia - Azhar, Nur Abidah (2018)
In Malaysia, the foundation design and piling method generally relies on the conventional method. However, the construction work sometimes contributed to some bad effects such as noise and vibration disturbance. Silent piling technology is the new piling method used in construction activities in Malaysia. This technology offers a very good future for foundation engineering construction. The objectives of this research are to study the level of acceptance and potential application of silent piling technology among local authorities in Malaysia. In order to achieve these objectives, a quantitative research by questionnaire and qualitative research by in-depth interview were conducted in this research. Hence, a mixed method design of the combination of quantitative and qualitative approaches was used in the data analysis. This study has found that generally this technology is needful. However, most of the respondents prefer to use other conventional method in which easily available and low cost. Interestingly, the majority of those who responded knew about silent piling technology and its potential benefits. In addition, over 80% of those who were interviewed indicated that Press-in piling is potentially the best solution in managing sustainable issues for construction. In conclusions, these findings have significant implications for adapting sustainable construction practice such as Press-in piling in Malaysia.